Medieval Visions of Space. Selected Aspects of Geographical Thought in the Middle Ages - Lewandowska, Lena (Vade Nobiscum, tom XXV/2025: Varia, 2025)
The aim of this article is to briefly discuss the perception of space in the Middle Ages. In its first part I will review the most important claims in the field of cosmography – the medieval response to pagan geography – and present the general model of the Earth and the Universe established in the Middle Ages, as well as its alternative visions. In the second part I’ll introduce the phenomenon of mappaemundi and indicate how the medieval visions of space would be realised in the form of the world maps form the epoque.